Permasalahan Pelaksanaan Manajemen Berbasis Sekolah pada Sekolah Dasar di Dabin Gugus Raden Sa’id Kabupaten Kudus - Kurniati Kurnitati; Achmad Hilal Madjdi; Siti Chumaidah (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2023)
School-based management is a way of managing educational institutions in terms of planning, implementing and evaluating education. MBS stands for , a policy approach that aims to shape school leadership by empowering school leaders and increasing community participation in efforts to improve school performance, including teachers, students, parents and the community. In this case, education management according to MBS is different from previous education management which is centralized in nature, while MBS provides broad autonomy to the school unit itself and involves the community to participate in advancing education in schools. In other words, all school policies and programs are determined by the school committee based on deliberations from members consisting of regional education officials, school principals, teachers, parents' representatives, community leaders, and regional officials where the school is located. The democratization of education is carried out by involving elements of the local government, community and parents in a partnership relationship and fostering positive support for madrasah education. At this level, the decentralization of education as a result of autode includes three important points, namely school-based management, delegation of authority, and educational innovation. The new paradigm in the field of education has pushed towards more humane educational goals. Educational autonomy has provided an opportunity for regions to be able to spur education in their respective regions. While in decentralized management, a lot of central, regional, and regional offices authority is handed over to schools. With this approach, schools will be more empowered and the decisions they make will be more effective and efficient. In the context of implementing SBM, school functions that were originally carried out by the government were partially decentralized to schools to run professionally. For this reason, schools need to build good relations with the community. Schools have programs that need to be introduced to the community, schools also accept criticism and suggestions from the community.